Numerical tests of steel beam-to-column semi-rigid connections - Urbonas, Kęstutis; Daniūnas, Alfonsas (Journal of Civil Engineering and Management, 2003)
This paper presents an analysis of semi-rigid beam-to-column connections in which the beam is connected to column not at 90 degrees angle. Beam-to-column bolted end-plate connections that are subjected to pure bending were modelled by three-dimensional finite elements. Numerical modelling of connection covers the geometrical and material non-linearities as well as contact and separation between various components of connection. Moment-rotation M-Φ curves for modelled connections using numerical results are made and stress distribution in connection components is presented. The study shows a significant influence of inclination of beam and quantity and location of bolts on the joint rigidity.First Published Online: 26 Jul 2012